Integrated microfluidic spectroscopic sensor using arrayed waveguide grating - Hu, Z.; Glidle, A.; Ironside, Charlie; Sorel, M.; Strain, M.; Cooper, J.; Yin, H. (SPIE, 2013)
With non-invasive properties and high sensitivities, portable optical biosensors are extremely desirable for point-of-care (POC) applications. Lab-on-a-chip technology such as microfluidics has been treated as an ideal approach to integrate complex sample processing and analysis units with optical detection elements. The work in this paper has developed an integrated dispersive component in combination with a microfluidic chip, providing a portable and inexpensive platform for on-chip spectroscopic sensing. We demonstrate an integrated microfluidic spectroscopic sensor by using an arrayed waveguide grating (AWG) device. In particular, a visible AWG device (?c=680nm) with chip size of 12.1mm by 1.5mm was designed and fabricated by employing flamed hydrolysis deposited (FHD) silica as the waveguide material. A straight input waveguide is used to perform device characterization while a perpendicular curved waveguide is employed to introduce laser excitation light. A polymer microfluidic chip is integrated with the AWG device by oxygen plasma bonding. To prove effectiveness of the integrated spectroscopic sensor, fluorescence spectrum of an organic fluorophore (Cy5) was tested. Reconstructed spectrum by using the AWG device is compared with the outcome from a conventional spectrometer and a good consistency is presented. © 2013 SPIE.